2014
DOI: 10.1093/mnras/stt2421
|View full text |Cite
|
Sign up to set email alerts
|

The eccentric massive binary V380 Cyg: revised orbital elements and interpretation of the intrinsic variability of the primary component*

Abstract: We present a detailed analysis and interpretation of the high-mass binary V380 Cyg, based on high-precision space photometry gathered with the Kepler space mission as well as highresolution ground-based spectroscopy obtained with the hermes spectrograph attached to the 1.2m Mercator telescope. We derive a precise orbital solution and the full physical properties of the system, including dynamical component mass estimates of 11.43±0.19 and 7.00±0.14 M ⊙ for the primary and secondary, respectively. Our frequency… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(100 citation statements)
references
References 70 publications
7
89
3
1
Order By: Relevance
“…This is in agreement with results on a sample of massive DEBs (Pavlovski & Hensberge 2005;Pavlovski & Southworth 2009Pavlovski et al , 2011Mayer et al 2013;Tkachenko et al 2014, with typical v rot sin i 100 km s −1 ), which also show no signs of mixing with CN-cycled matter. Mixing signatures are found in the remaining 1/3 of our sample stars.…”
Section: Evolutionary Status Of the Sample Starssupporting
confidence: 91%
See 1 more Smart Citation
“…This is in agreement with results on a sample of massive DEBs (Pavlovski & Hensberge 2005;Pavlovski & Southworth 2009Pavlovski et al , 2011Mayer et al 2013;Tkachenko et al 2014, with typical v rot sin i 100 km s −1 ), which also show no signs of mixing with CN-cycled matter. Mixing signatures are found in the remaining 1/3 of our sample stars.…”
Section: Evolutionary Status Of the Sample Starssupporting
confidence: 91%
“…The most accurate and precise fundamental parameters for massive stars available at present can be found in the compilation by Torres et al (2010, henceforth abbreviated TAG10), mainly for the most common among them, the early B-type stars of spectral types B0 to B3. Data on abundances of individual chemical elements in massive DEBs are scarce, though ongoing projects promise to alleviate the situation (Pavlovski & Hensberge 2005;Pavlovski & Southworth 2009Pavlovski et al , 2011Mayer et al 2013;Tkachenko et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…A study of the correlation between α ov and mass by Ribas et al (2000) used a total of eight DLEBs with component masses in the range 2-12 M , and found a strong dependence of the extra mixing on mass. These authors relied very heavily on the massive binary V380 Cyg (M 1 ∼ 11 M , M 2 ∼ 7 M ) to establish the slope of the relation, however, fitting the measured properties of this critical system has always been problematic, as discussed at length by Claret (2007) and also more recently by Tkachenko et al (2014). The latter authors reported a new set of precise determinations of the mass, radius, temperature, chemical composition, and other properties of the components that have nevertheless remained difficult to reconcile with models.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the authors found that the position of the more evolved primary component in the Kiel diagram can only be explained when a large amount of extra mixing in terms of the overextension of the convective core (core overshoot α) is included in the models. The system has been recently revisited by [31] based on high-quality space-based Kepler photometry and ground-based, highresolution hermes [27] spectroscopy. The authors found that the evolutionary tracks computed for the dynamical masses of the stars fail to explain their positions in the Kiel diagram (see Fig.…”
Section: Mass Discrepancymentioning
confidence: 99%
“…Thanks to the fact that many pulsating stars are found in binary systems across the whole HR-diagram, binary stars -systems consisting of two stellar objects that periodically revolve around their common center of mass -can provide us with additional, model-independent observational constraints in terms of the dynamical masses and radii of stars. Nowadays, we talk about dynamical measurements of fundamental properties of stars in large mass and age ranges to precisions approaching 1% [e.g., 15,31]. This way, asteroseismic investigations can be confronted/supplied with model-independent fundamental properties of stars, providing a valuable test of the current theories of stellar structure and evolution.…”
Section: Introductionmentioning
confidence: 99%